Global Partnership Under a New Normal: Challenges and Response to COVID-19 - Hasan, Nik Norma Nik; Hamzah, Aswati (Springer International Publishing, 2020)
Sustainability Development Goal (SDG) 17 Partnership is a voluntary and collaborative effort between various parties, both public and nonpublic, in which all participants agree to work together to achieve a common purpose or undertake a specific task, as mutually agreed, to share risks and responsibilities, resources and benefits (UN 2016a).